Compton spectroscopy and electronic structure study for tetragonal barium titanate. (May 2019) - Meena, Seema Kumari; Dashora, Alpa; Heda, N.L.; Ahuja, B.L.
Abstract: The Compton profile of tetragonal BaTiO3 is measured using 20Ci 137 Cs Compton spectrometer. The experimental data have been analyzed using theoretical electron momentum densities computed using linear combination of atomic orbitals (LCAO) with density functional theory (DFT) and the hybridization of Hartree-Fock and DFT (WC1LYP scheme). It observed that hybrid scheme WC1LYP provides a better agreement with the experimental data than other approximations of exchange-correlation (with generalized gradient approximation like PBESol, SOGGA and local density approximation like LDAPZ) as considered in the present work. In addition, the energy bands and density of states have been reported using LCAO-WC1LYP scheme. The WC1LYP hybrid method confirms wide band gap semiconducting nature of tetragonal BaTiO3 . Further, a relative nature of bonding among CaTiO3, SrTiO3 and BaTiO3 has also been discussed using equal-valence-electron-density profiles and Mulliken's population analysis which predict a trend of increasing iconicity in the order CaTiO3 →BaTiO3 →SrTiO3 . Highlights: Measured first-ever Compton profile (CP) of tetragonal BaTiO3 using high energy γ-rays. Compared experimental CPs with those from LCAO-DFT and hybrid calculations. Discussed applicability of hybrid functionals for BaTiO3 . Discussed relative nature of bonding using Mulliken's population and EVED profiles.